HUBUNGAN AKTIVITAS FISIK DENGAN LINGKAR PINGGANG PADA REMAJA TINGKAT DI SMA NEGERI 76 JAKARTA - Indah Septiyani (2022)
The aim of this research is to knowing the relationship between physical activity and waist circumference of high school youth in Jakarta. The research design in this scientific paper is cross-sectional, which is a type of research in which the data will be analyzed using a questionnaire that has been collected as it is. Data were analyzed by statistical test. Kolmogorov-Smirnov and correlation test using Spearman. The implementation is through an email survey with reference to the GPAQ questionnaire (Global Physical Activity Questionnaire) which is carried out once data collection where the research object is measured simultaneously at the same time. The samples tested were 67 people from SMA Negeri Jakarta. This study uses objective analysis and direct measurements to determine the prevalence of the relationship between waist circumference and physical activity in adolescents at SMA Negeri Jakarta. The results of this study were reviewed from the respondent's characteristics, physical activity, waist circumference measurement, and the relationship between physical activity and waist circumference which showed the conclusion that the relationship between physical activity and waist circumference showed insignificant results.